Project-Based Learning dan Kecerdasan Linguistik Kunci Sukses Terhadap Kemampuan Menyusun Teks Narasi Siswa - Muslihatun, Muslihatun; Padlurrahman, Padlurrahman; Murcahyanto, Hary (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT This study aims to evaluate the effectiveness of the Project-Based Learning (PJBL) model in improving linguistic intelligence and narrative text writing skills among junior high school students. The research employs an experimental method with a quantitative approach, involving junior high school students divided into two groups: the experimental group (using PJBL) and the control group (conventional learning). Data were collected through pre- and post-intervention narrative writing tests. The results show that students who participated in PJBL experienced significant improvements in linguistic intelligence and narrative text writing skills compared to the control group. PJBL encourages students to be more active, think critically, and creatively in writing, while deepening their understanding of text structure and vocabulary. In conclusion, PJBL has been proven effective in enhancing junior high school students' narrative writing abilities and linguistic intelligence, and it is recommended to be integrated into language learning. Keywords: Linguistic intelligence, Writing skills, PJBL, Narrative text.